Extracellular vesicles in embryo implantation and disorders of the endometrium. (4th November 2020) - Mishra, Anuradha; Ashary, Nancy; Sharma, Richa; Modi, Deepak
Abstract: Implantation of the embryo is a rate‐limiting step for a successful pregnancy, and it requires an intricate crosstalk between the embryo and the endometrium. Extracellular vesicles (EVs) are membrane‐enclosed, nano‐sized structures produced by cells to mediate cell to cell communication and modulate a diverse set of biological processes. Herein, we review the involvement of EVs in the process of embryo implantation and endometrial diseases. EVs have been isolated from uterine fluid, cultured endometrial epithelial/stromal cells and trophectodermal cells. The endometrial epithelial and stromal/decidual cell‐derived EVs and its cargo are internalized bythe trophoblast cells, and they regulate a diverse set of genes involved in adhesion, invasion and migration. Conversely, the embryo‐derived EVs and its cargo are internalized by epithelial and immune cells of the endometrium for biosensing and immunomodulation required for successful implantation. EVs have also been shown to play a role in infertility, recurrent implantation failure, endometriosis, endometritis and endometrial cancer. Further research should set a stage for EVs as non‐invasive "liquid biopsy" tools for assessment of endometrial health.